2022
DOI: 10.13189/saj.2022.100226
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Reactive Agility Measurements of Tennis Performance

Abstract: Reactive agility measurement tool recently has become one of the important issues in the physical training for tennis performance. Therefore, finding a valid and reliable reactive agility measuring instrument for tennis performance is needed. This study aimed to do a validity and reliability test of the reactive agility measuring instrument for tennis performance. This study used a mixed-methods approach. The seven experts participants were determined by the criteria of an evaluation expert and a tennis expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This study found that the table tennis eye-hand coordination measuring instrument has good content validity and can be used to measure the eye-hand coordination of table tennis athletes. The results of this study follow the results of research by Nugroho et al [26]. The results of the expert assessment instrument get a value of > 0.76, so it can be said that the aspect has good content validity.…”
Section: Discussionsupporting
confidence: 86%
“…This study found that the table tennis eye-hand coordination measuring instrument has good content validity and can be used to measure the eye-hand coordination of table tennis athletes. The results of this study follow the results of research by Nugroho et al [26]. The results of the expert assessment instrument get a value of > 0.76, so it can be said that the aspect has good content validity.…”
Section: Discussionsupporting
confidence: 86%
“…Based on the literature review from several international journals using thematic analysis, the resulting concept of sensor-based reactive agility was found to be the speedy direction change in short side steps or sprints after receiving an unplanned stimulus (Inglis & Bird, 2016;Matlák et al, 2017;Nugroho et al, 2022;Spiteri et al, 2015). Additionally, the concept and blueprint for the construction of a sensor-based reactive agility measurement tool for net game sports groups were obtained, as shown in Figure 1 below: The test subject prepares to start in the purple box, facing the four lights.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Research on competitive performance in net game sports has demonstrated its links to the characteristics of fast short movements, acceleration, and quick changes in direction (Qowiyyuridho, Tomoliyus, & Fauzi, 2021). Attempting to define reactive agility some practitioners insinuated that it refers to rapid whole-body movement with a change in speed and direction after responding to a stimulus (Nugroho, Tomoliyus, Alim, Fauzi, & Yuliarto, 2022). Reactive agility incorporates a cognitive component by involving perception and reaction to cues indicating the direction of a turn (Spiteri, Newton, & Nimphius, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tennis is an intermittent sport that requires acceleration, reaction, and balance for repetitive and varied strokes in different corners of the court [1]. Tennis is one of the sports that has many enthusiasts in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Movement coordination errors create obstacles to the transfer of force from the legs to the body segments and are passed on to the ball [9]. Complex movements require good coordination, balance, and motor qualities to reach optimal levels [1] [10].…”
Section: Introductionmentioning
confidence: 99%